Modelling of Escherichia coli Density on Land and Concentration in Surface Runoff - Ling, Teck Yee; Bengtson, R. L.; Drapcho, C.M.; Achberger, E.C.; Sabbagh, G.J.; Jackson, J. (Malaysian Journal of Soil Science, 2006)
Integrated fanning of crop and animal enables (eSources from animal waste to be utilised. However, bacterial pollution is a concern.In this study, a bacterial model,ECOLI, was developed to simulate Escherichia coli density daily on land and its concentration in surface runoff. Loss of E. coli was assumed to occur through decay,runoff, sediment and percolation. E. coli decay was assumed to follow the first order decay affected by soil pH, soil. tempcirature and soil moisture.In testing the model, the ECOLI model was interfaced with the GLEAMS-SWT hydrologic and erosion model. Calibration and evaluation was performed with field-scale data from Franklinton, Louisiana. Fresh cow manure· was applied on grassed plots and runoff was collected and analysed. Predicted E.coli concerntrations versus observed E. coli centrations in surface runoff gave a regression line with coefficient of determination of 0.993, intercept of 0.011 and a slope of 0.995 indicating good agreement of model predicted conCentrations with observed concentrations. The ECOLI model can be used to study die effects of various animal waste application practices such as waste loading rate, timing of application and frequency of application. More research needs to be conducted to incorporate databases so as to expand the capabilities of this model.